Terminação de novilhos aos 18 meses de idade, suplementados em pastagem de sorgo forrageiro - Silva, Viviane Santos da (2015)
This study aimed to evaluate the effects of three levels of supplementation offered in a quantity equivalent to 0.8%, 1.0% or 1.2 % of live weight on the performance, body development, and ingestive behavior and displacement pattern of 24 steers, with initial average age and weight of 16 months and 334.58 kg kept in continuous grazing in sorghum forage pasture (Sorghum bicolor). The completely randomized design was used with parcels subdivided in time, constituting of three treatments and four repetitions of area (spot) per treatment, and four repetitions (animals) per treatment on the analysis of ingestive behavior and displacement. No difference was observed for daily weight gain (1.188 kg day-1) and stocking rate (894.80 kg LW ha-1) among the studied treatments. The average weight gain per total area was 201.10 kg ha-1 between the treatments, however at the first period it was observed a gain of 113 kg ha-1 (P<0.05), not differing at the second and third periods (48.21 kg ha-1). It was observed greater leaf blades mass of sorghum (670.69 kg DM ha-1) and sorghum accumulation rate (77.83 kg DM ha-1 day) at the first 28 days of utilization of the pasture, being constant at the second and third periods (470.55 kg DM ha-1 and 53,52 kg DM ha-1 day, respectively). No difference was observed on the final body measures, frame and weight: height relation of the animals according to the level of supplementation. The advance of the phenotype cycle of the pasture promotes the decrease on the leaf blades mass, accumulation rate and an increase on the forage mass of others. The steers that received the equivalent to 0.8% of live weight in supplementation presented higher (P<0.05) grazing time during the morning shift (241.25 min. morning-1) compared to the animals of the 1.2% treatment that spent 172.5 min. morning-1 in this activity, while the 1% treatment remained intermediate (205. 42 min. morning-1). The grazing time decreased (P<0.05) with the increase of the utilization of the pasture, with averages of 565.83; 494.09 and 437.5 min. day-1 for the first, second and third periods, respectively. The idle time increased (P<0.05) from the first (423.33 min day-1) to the second and third periods (557.06 min. day-1). The levels of supplementation did not influenced the variables of displacement, however the structural variation of the pasture, influenced on the biting rate min-1 and the number of bitings per feed-1 station.